Predictors for tooth loss in periodontitis patients: Systematic review and meta‐analysis. (28th May 2019) - Helal, Omar; Göstemeyer, Gerd; Krois, Joachim; Fawzy El Sayed, Karim; Graetz, Christian; Schwendicke, Falk
Abstract: Aim: A range of predictors for tooth loss in periodontitis patients have been reported. We performed a systematic review and meta‐analysis to assess the consistency and magnitude of any association between a total of 12 predictors and tooth loss. Materials and Methods: Medline/Embase/Central were searched for longitudinal studies investigating the association between predictors and tooth loss in periodontitis patients. Random‐effects meta‐analysis was performed, and study quality assessed. Results: Twenty studies (15, 422 patients, mean follow‐up: 12 years) were included. The mean annual tooth loss/patient was 0.12 (min./max: 0.01/0.36). Older patients ( n  = 8 studies; OR: 1.05, 95% CI: 1.03–1.08/year), non‐compliant ones ( n  = 11; 1.51, 1.06–2.16), diabetics ( n  = 7; 1.80, 1.26–2.57), those with IL‐1‐polymorphism ( n  = 3; 1.80; 1.29–2.52) and smokers ( n  = 15; 1.98, 1.58–2.48) had a significantly higher risk of tooth loss. Teeth with bone loss ( n  = 3; 1.04, 1.03–1.05/%), high probing pocket depth ( n  = 6; 3.19, 1.70–5.98), mobility ( n  = 4; 3.71, 1.65–8.38) and molars ( n  = 4; 4.22, 2.12–8.39), especially with furcation involvement ( n  = 5; 2.68, 1.75–4.08) also showed higher risks. Gender ( n  = 16; 0.95, 0.86–1.05) and endodontic affection ( n  = 3; 3.62, 0.99–13.2) were not significantly associated with tooth loss. Conclusions: Older, non‐compliant, smoking or diabetic patients, and teeth with bone loss, high probing pocket depth, mobility, or molars, especially with furcation involvement showed higher risks of tooth loss.